The Influences of Different Parameters on the Static and Dynamic Performances of the Aerostatic Bearing - Jianbo Zhang; Zhifang Deng; Kun Zhang; Hailiang Jin; Tao Yuan; Ce Chen; Zhimin Su; Yitao Cao; Zhongliang Xie; Danyang Wu; Jingping Sui (Lubricants, 2023)
Aerostatic bearings have been widely applied to high-rotating speed machines due to their low friction and high rotational speed advantages. The geometry parameters, supply pressure and rotational speed play important roles in the static and dynamic performances of the aerostatic bearings. In this paper, the steady state and dynamic Reynolds equations are solved by the finite difference method (FDM) and used to study the static and dynamic performances of the aerostatic bearings. Then, combined with the motion equation of the rigid rotor-aerostatic bearing system, the linear stability of the aerostatic bearing is also studied. Moreover, based on the theory mentioned above, the influences of the geometry parameters (such as orifice diameter, radial clearance and eccentricity), rotational speed and supply pressure are investigated in detail. It was found that aerostatic bearing geometries, rotational speed and supply pressure had a significant effect on the steady and dynamic performances. Under the low-speed conditions and high supple pressure, the static pressure effect plays the main role in the performances of the aerostatic bearings, while on the contrary, the rotational effect plays the main role. Furthermore, a half-speed whirl may generate under certain conditions. The results also provide useful design guidelines for aerostatic bearings in high-speed machines.